Plant Antiviral Immunity Against Geminiviruses and Viral Counter-Defense for Survival - Kumar, R. Vinoth (Frontiers in Microbiology, 2019)
The family Geminiviridae includes plant-infecting viruses whose genomes are composed of one or two circular non-enveloped ssDNAs(+) of about 2.5-5.2 kb each in size. These insect-transmissible geminiviruses cause significant crop losses across continents and pose a serious threat to food security. Under the control of promoters generally located within the intergenic region, their genomes encode five to eight ORFs from overlapping viral transcripts. Most proteins encoded by geminiviruses perform multiple functions, such as suppressing defense responses, hijacking ubiquitin-proteasomal pathways, altering hormonal responses, manipulating cell cycle regulation, and exploiting protein-signaling cascades. Geminiviruses establish complex but coordinated interactions with several host elements to spread and facilitate successful infection cycles. Consequently, plants have evolved several multilayered defense strategies against geminivirus infection and distribution. Recent studies on the evasion of host-mediated resistance factors by various geminivirus proteins through novel mechanisms have provided new insights into the development of antiviral strategies against geminiviruses. This review summarizes the current knowledge concerning virus movement within and between cells, as well as the recent advances in our understanding of the biological roles of virus-encoded proteins in manipulating host-mediated responses and insect transmission. This review also highlights unexplored areas that may increase our understanding of the biology of geminiviruses and how to combat these important plant pathogens.